The Impact of Bina Keluarga Lansia Program on the Quality of Life of Elderly in Sleman, Yogyakarta (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
Indonesian government, through BKKBN, has joined to promote healthy life in the elderly in the community. Bina Keluarga Lansia (BKL) programme was established to fulfil elderly need through a family-based approach. This study is aimed to evaluate the programme with the examination of the quality of life of its members, including the elderly and their family member. We used a cross-sectional method using WHO-QOL BREF questionnaire to assess the quality of life and another questionnaire to enlist the involvement on the BKL activities. This study was conducted in 2018, at four BKL groups across Sleman Regency. Further analysis was conducted with gaussian mix models to adjust for the cluster effect from sampling method. Our 103 respondents with 68 family members and 35 elderly generally have a good quality of life on four dimensions of WHO-QOL BREF. We found that BKL activities statistically significant associated with better QoL, especially in Social Domain and Psychological Domain. Activities that were specifically associated with better QoL was health education on elderly resilience and art/music activities. Other activities that show borderline association was business activities. BKL programme has shown an association with better QoL, thus any successful activities should be maintained or improved, and other less influential activities should be reviewed and customised with local needs.